AEA Randomized Controlled Trials 2019
DOI: 10.1257/rct.4454-1.0
|View full text |Cite
|
Sign up to set email alerts
|

Do role models increase student hope and effort? Evidence from India

Abstract: This paper offers experimental evidence on the significance of role-models on fostering hope, increasing effort and improving the academic performance of primary school students in India.Students from private schools were individually randomised to a treatment or a placebo group.Treated students watch a short film produced as a part of the experiment in Jaipur, Rajasthan -the study location. The placebo group students watch a television show for kids, 'Malgudi Days'. I find a 0.17 standard deviation (s.d.) inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Theoretical work such as Ray (2006), Dalton et al (2016), Genicot and Ray (2017) and Lybbert and Wydick (2018) has provided a framework for understanding the role that aspirations may play in development settings. At the same time, experimental work has sought to understand whether light-touch aspirations interventions are able to increase investments in education and family enterprises (Bernard et al, 2014;Janzen et al, 2017;Riley, 2017;Aguinaga et al, 2019;Batista and Seither, 2019;Bhan, 2020;Orkin et al, 2021;and Rojas et al, 2022), where this new body of research has generally found modest to strong impacts from interventions that highlight the achievements of potential role models who in other ways are similar to the subjects. 1 Our research seeks to contribute to this emerging literature through a coaching intervention among Bolivian dairy farmers, involving a video-based documentary, that emphasizes role-modeling and aspiring to best dairy-farming practices and higher levels of milk production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical work such as Ray (2006), Dalton et al (2016), Genicot and Ray (2017) and Lybbert and Wydick (2018) has provided a framework for understanding the role that aspirations may play in development settings. At the same time, experimental work has sought to understand whether light-touch aspirations interventions are able to increase investments in education and family enterprises (Bernard et al, 2014;Janzen et al, 2017;Riley, 2017;Aguinaga et al, 2019;Batista and Seither, 2019;Bhan, 2020;Orkin et al, 2021;and Rojas et al, 2022), where this new body of research has generally found modest to strong impacts from interventions that highlight the achievements of potential role models who in other ways are similar to the subjects. 1 Our research seeks to contribute to this emerging literature through a coaching intervention among Bolivian dairy farmers, involving a video-based documentary, that emphasizes role-modeling and aspiring to best dairy-farming practices and higher levels of milk production.…”
Section: Introductionmentioning
confidence: 99%
“…These interventions have exposed participants to role models, often through recorded video, based on the premise that aspirations are determined by observing others who are relatively better-off (Ray, 2006). Along with the pioneer intervention by Bernard et al (2014) in Ethiopia showcasing successful entrepreneurs, subsequent studies have been carried out by Lubega et al (2017) on preventing HIV infection in Uganda, Batista and Seither (2019) on fostering entrepreneurialism in Mozambique, and Bhan (2020) on creating aspirations for school children in India. In research on microcredit recipients in Mexico, Rojas et al (2022) add two components to the video intervention: a refrigerator magnet to write goals and a series of workshops on aspirational hope.…”
Section: Introductionmentioning
confidence: 99%